2021
DOI: 10.1055/a-1447-0264
|View full text |Cite
|
Sign up to set email alerts
|

MRI-findings in idiopathic intracranial hypertension (Pseudotumor cerebri)

Abstract: Background Pseudotumor cerebri, also known as idiopathic intracranial hypertension, is a disorder of increased intracranial pressure of unknown etiology. Main symptom is headache which has a characteristic similar to other headache diseases, therefore the idiopathic intracranial hypertension often remains undetected. The incidence is 1/100 000 with the number of unreported cases being much higher. This article highlights the essential role of MRI in the differential diagnosis. Methods A literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
(118 reference statements)
0
9
0
1
Order By: Relevance
“…The frequency of MRI abnormalities of nearly 80% of the cases in our study is close to what has been shown in previous studies. 23 , 24 MRI is a very useful method to aid in the diagnosis of this entity, however, its role in the prognostic assessment of IIH remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of MRI abnormalities of nearly 80% of the cases in our study is close to what has been shown in previous studies. 23 , 24 MRI is a very useful method to aid in the diagnosis of this entity, however, its role in the prognostic assessment of IIH remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Nonne's intent was to propose a state of elevated intracranial pressure that was distinct from that related to cerebral tumors: intercranial hypertension that followed a less sinister course. 11 John Foley 12 later offered the term "benign intracranial hypertension. "…”
Section: Intracranial Hypertensionmentioning
confidence: 99%
“…Dural venous sinus stenoses or thromboses (Figure 5) were described in patients with clinical features of IIH. It is still not clear if increased intracranial venous pressure is a cause or a consequence of elevated intracranial pressures with contradictory results in the literature 16 . Therefore, MRV or CTV is recommended in patients with pulsatile tinnitus and a clinical suspicion of IIH to evaluate for dural venous sinus stenosis or thrombosis 8 .…”
Section: Differential Diagnosis and Imaging Findings In Pulsatile Tin...mentioning
confidence: 99%
“…It is still not clear if increased intracranial venous pressure is a cause or a consequence of elevated intracranial pressures with contradictory results in the literature. 16 Therefore, MRV or CTV is recommended in patients with pulsatile tinnitus and a clinical suspicion of IIH to evaluate for dural venous sinus stenosis or thrombosis. 8 Additional MRI findings of IIH include an empty sella and evidence of papilledema, prominent optic nerve sheaths, flattening of the posterior globe, and tortuous optic nerves (Figure 6).…”
Section: Idiopathic Intracranial Hypertension and Dural Venous Sinus ...mentioning
confidence: 99%
See 1 more Smart Citation